2002
DOI: 10.1021/ma011951f
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide End-Capping Using Functionalized Isocyanates:  Preparation of Pentablock Copolymers

Abstract: The use of electrophiles (isocyanates, isothiocyanates, acid chlorides) to cap the N-terminal ends of polypeptides and the use of isocyanates to prepare poly(γ-benzyl-L-glutamate)-b-(nonpeptide polymer) block copolymers are described. This chemistry was also used to prepare poly(ethylene glycol)where polymer ) polyoctenamer, poly(ethylene glycol), or poly(dimethylsiloxane). These R,ω-diamino-terminated polymers (polymer) were used to prepare difunctional macroinitiators for the living polymerization of γ-benzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 17 publications
0
62
0
4
Order By: Relevance
“…It is wellknown in NCA polymerizations that electrophiles, such as isocyanates, act as chain terminating agents by reaction with the propagating amine chain-ends [9]. Deming and coworkers reported that the reactive living nickelacycle polypeptide chain-ends could be quantitatively capped by reaction with excess isocyanate, isothiocyanate, or acid chloride [33]. Using this chemistry, they prepared isocyanate end-capped poly(ethylene glycol), PEG, and reacted this, in excess, with living poly(γ -benzyl-L-glutamate), PBLG, to obtain PBLG-b-PEG diblock copolymers (Eq.…”
Section: Insert Equationmentioning
confidence: 99%
“…It is wellknown in NCA polymerizations that electrophiles, such as isocyanates, act as chain terminating agents by reaction with the propagating amine chain-ends [9]. Deming and coworkers reported that the reactive living nickelacycle polypeptide chain-ends could be quantitatively capped by reaction with excess isocyanate, isothiocyanate, or acid chloride [33]. Using this chemistry, they prepared isocyanate end-capped poly(ethylene glycol), PEG, and reacted this, in excess, with living poly(γ -benzyl-L-glutamate), PBLG, to obtain PBLG-b-PEG diblock copolymers (Eq.…”
Section: Insert Equationmentioning
confidence: 99%
“…Similar strategies could be used to create this topology with a hydrophilic homopeptide, synthesized through ROP of NCAs, employing a small molecule diamine initiator as the center block and either a hydrophobic synthetic polymer/polypeptide as the outer blocks. In addition to the coupling chemistry used by Kiick, Deming et al 94 have used amine-isocyanate chemistries to proficiently create polypeptide multiblock hydrid polymers.…”
Section: Synthetic Techniques For Polypeptide-based Copolymers With Tmentioning
confidence: 99%
“…Im Falle der a-Aminosäure-NCAs gelang neben der Herstellung von Homopolypeptiden [99,100] die Synthese zahlreicher Diblock-, Triblock-und PentablockCopolypeptide. [101][102][103][104][105][106][107][108][109][110][111][112][113] Struktur und Eigenschaften dieser Blockcopolypeptide werden in Abschnitt 6 kommentiert.…”
Section: Neue Metallorganische Initiatorenunclassified